2010
DOI: 10.1111/j.1600-0765.2010.01277.x
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate, a bacterial metabolite, induces apoptosis and autophagic cell death in gingival epithelial cells

Abstract: These data suggest that butyrate induces apoptosis and autophagic cell death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(95 citation statements)
references
References 32 publications
4
90
1
Order By: Relevance
“…Short-chain fatty acids can disrupt host defense systems by different mechanisms, such as induction of apoptosis in immune cells (Stehle et al, 2001;Abe, 2012) and gingival epithelial cells (Tsuda et al, 2010) and alteration of cell function and gene expression in human gingival fibroblasts (Chang et al, 2013). Previous studies have demonstrated higher concentrations of short-chain fatty acids in the gingival crevicular fluid of periodontitis patients (Lu et al, 2008;Qiqiang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Short-chain fatty acids can disrupt host defense systems by different mechanisms, such as induction of apoptosis in immune cells (Stehle et al, 2001;Abe, 2012) and gingival epithelial cells (Tsuda et al, 2010) and alteration of cell function and gene expression in human gingival fibroblasts (Chang et al, 2013). Previous studies have demonstrated higher concentrations of short-chain fatty acids in the gingival crevicular fluid of periodontitis patients (Lu et al, 2008;Qiqiang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that butyrate concentrations of 0.5 mM or higher induce death of epithelial cells (70). Although some dead cells exhibit features of apoptosis, such as phosphatidylserine redistribution, increased caspase-3 activity, and decreased anti-apoptotic bcl-2 expression, only a small number were rescued by treatment with zVAD-fmk, a pan-caspase inhibitor (70). We also observed induction of a couple of autophagic features by butyrate, such as autophagic flux and increased-LC3 lipidation (70).…”
Section: Possible Relationship Of Cell Death To Periodontal Diseasementioning
confidence: 91%
“…Although some dead cells exhibit features of apoptosis, such as phosphatidylserine redistribution, increased caspase-3 activity, and decreased anti-apoptotic bcl-2 expression, only a small number were rescued by treatment with zVAD-fmk, a pan-caspase inhibitor (70). We also observed induction of a couple of autophagic features by butyrate, such as autophagic flux and increased-LC3 lipidation (70). Furthermore, cell death was reduced by the autophagy inhibitor 3-methyladenine, which suggests that butyrate induced autophagic cell death of gingival epithelial cells (70).…”
Section: Possible Relationship Of Cell Death To Periodontal Diseasementioning
confidence: 99%
“…In addition to energy production, amino acid metabolism is important for understanding bacterial virulence, because the end products of short-chain fatty acids, e.g. butyrate, exhibit cytotoxicity against periodontal epithelial cells (14). In fact, the concentration of butyrate is increased in subgingival fluid in periodontal patients (15), and these compounds are proposed to be involved in the initiation and progression of these diseases (16).…”
mentioning
confidence: 99%